2004
DOI: 10.1152/ajpregu.00725.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary gas exchange at maximal exercise in Danish lowlanders during 8 wk of acclimatization to 4,100 m and in high-altitude Aymara natives

Abstract: -We aimed to test effects of altitude acclimatization on pulmonary gas exchange at maximal exercise. Six lowlanders were studied at sea level, in acute hypoxia (AH), and after 2 and 8 wk of acclimatization to 4,100 m (2W and 8W) and compared with Aymara high-altitude natives residing at this altitude. As expected, alveolar PO2 was reduced during AH but increased gradually during acclimatization (61 Ϯ 0.7, 69 Ϯ 0.9, and 72 Ϯ 1.4 mmHg in AH, 2W, and 8W, respectively), reaching values significantly higher than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 28 publications
10
113
0
Order By: Relevance
“…However, peak exercise V E in altitude-acclimatized lowlanders may be similar (Calbet et al, 2003b), higher (Marconi et al, 2004), or slightly lower than observed in normoxia (Lundby et al, 2004a).…”
Section: Exercise V E In Chronic Hypoxiamentioning
confidence: 72%
See 2 more Smart Citations
“…However, peak exercise V E in altitude-acclimatized lowlanders may be similar (Calbet et al, 2003b), higher (Marconi et al, 2004), or slightly lower than observed in normoxia (Lundby et al, 2004a).…”
Section: Exercise V E In Chronic Hypoxiamentioning
confidence: 72%
“…Compared to acute hypoxia, submaximal exercise V E remains at the same level with altitude acclimatization, while peak exercise V E is increased at moderate to high altitudes (Calbet et al, 2003b;Marconi et al, 2004) and reduced at 4000 m (Lundby et al, 2004a). However, peak exercise V E in altitude-acclimatized lowlanders may be similar (Calbet et al, 2003b), higher (Marconi et al, 2004), or slightly lower than observed in normoxia (Lundby et al, 2004a).…”
Section: Exercise V E In Chronic Hypoxiamentioning
confidence: 80%
See 1 more Smart Citation
“…Blood sampling from the highaltitude natives was done at 4100·m. For further details see Lundby et al (2004).…”
Section: Arterial Blood Samplingmentioning
confidence: 99%
“…With sojourns at altitude over several days, the resting cardiac output normalizes through a decrease in stroke volume, which is attributed to a hypoxia-induced reduction in plasma volume and thus lower left ventricular end-diastolic volume (55). Ventilation and heart rate, however, remain increased even after acclimatization mediated by a sustained sympathetic response driven by peripheral chemoreceptors sensitized by the persistent hypoxemia (25,26,33). Under exercise, these adaptive mechanisms are additionally stressed, and performance is, therefore, limited in the hypoxic environment at altitude.…”
Section: Introductionmentioning
confidence: 99%